“Discharge doesn’t mean the end”: Exploring success in discharge to community self-management for young adults living with chronic pain: A qualitative study - Souraiya Kassam; Emi Wong; Marysa Thompson; Todd Tran; Rachael Bosma; Sarah Sheffe (Canadian Journal of Pain)
Background Living with chronic pain as a young adult (YA) can impact the physical, emotional, social, cognitive, and role function domains of life. Once YAs receive care for their specialist chronic pain care they are expected to self-navigate a complex health care system to transition to community-based care (i.e. primary care). Inadequate discharge planning may increase the unique difficulties YAs face in self-management, which may lead to adverse health outcomes, suboptimal discharge, and a need to reaccess care.Aims The purpose of this qualitative study is to explore how YAs with chronic pain define a successful discharge transition from a health service delivery model of specialized chronic pain services setting to self-management in a community setting (i.e. primary care) and contextual factors that promote discharge success.Methods This qualitative study included young adults with chronic pain. Data were obtained through semistructured interviews, which were transcribed verbatim and analyzed using inductive content analysis.Results Ten participants identified that successful discharge includes the following considerations: (1) acknowledging the tension between moving forward and looking back, (2) a collaborative discharge process, and (3) the need for ongoing, relevant resources and support.Conclusion This study provides a deeper understanding of how YAs with chronic pain characterize success in the discharge transition from specialized chronic pain services to community self-management. Our findings highlight the importance of provider–patient collaboration during the discharge planning process to develop a patient-centered self-management plan that incorporates community resources tailored to the needs of the individual to promote an optimal discharge.